AAR552: Modern Movement And Contemporary Architecture / Faculty of Architecture, Planning & Surveying - UiTM, Faculty of Architecture, Planning & Surveying (Universiti Teknologi MARA (UiTM), 2023)
This course examines the development of contemporary architecture and its evolution from the days of Bauhaus and the Modern Movement to the present digital age. It also highlights major world events (whether political, social, economics, scientific or technological) that help to shape the scenario of architecture throughout the world. The study also highlights famous architects and personalities that have made significant contributions to contemporary architecture within this period.